AMOUNT AND TYPE OF MICROBES ON THE COMMON CARP (Cyprinus carpio) IN JATILUHUR RESERVOIR WEST JAVA - Indah Nurwulan; Eddy Afrianto; Iis Rostini; Intan Pratama (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This research was conducted in Microbiology Laboratory of Biology Department, Faculty of Mathematics and Natural Sciences, Padjadjaran University in May 2017. The purpose of the research was to identify the number and types of microbes contained in carp (Cyprinus carpio) in Jatiluhur Reservoir, West Java. The method used in this research was sample survey method or field survey. The water and common carp sampling stations are divided into 3 stations, station 1 is located in Zone 1 (low density), station 2 is located in Zone 3 (medium density), and station 3 is located in Zone 5 (high density). Determination of sampling location water and fish is done based on Data Recapitulation of Density of Karamba Floating Net from the Department of Animal Husbandry and Fisheries of West Java.Water samples and fish mucus were tested using Total Plate Count (TPC) method using different specific media that is Trypticase Soy Agar (TSA), deMann Ragosa Sharpe Agar (MRSA), Kliger Iron Agaar (KIA), Thiosulphate Citrate Bile salts Sucrose Agar (TCBS), and Xylose Lysine Deoxycholate (XLD). Microbes can be known by species because they just grown on specific media that can directly showed the specific characteristics of certain microbial species based on the color of the colony. The parameter observed were microbiological test (TPC). The result of the research showed that there was Bacillus sp, Escherichia coli, Lactobacillus sp, Vibrio cholerae, Vibrio parahemoliticus, Vibrio spp, dan Shigella sp on the water samples and carp mucus. The result of research on water samples and fishery products in Jatiluhur Reservoir showed that water quality in Zone 1, Zone 3, and Zone 5 is still below the threshold of microbial contamination based on SNI 7388: 2009, while fish located in Zone 3 and Zone 5 is contaminated by Escherecia coli and Vibrio cholerae, exceed the threshold of SNI 7388: 2009 on microbial contamination in fresh fish.